2023
DOI: 10.3389/fcvm.2023.1160089
|View full text |Cite
|
Sign up to set email alerts
|

Differences in phenotypes, symptoms, and survival in patients with cardiomyopathy—a prospective observational study from the Sahlgrenska CardioMyoPathy Centre

Abstract: IntroductionCardiomyopathy is the fourth most common cause of heart failure. The spectrum of cardiomyopathies may be impacted by changes in environmental factors and the prognosis may be influenced by modern treatment. The aim of this study is to create a prospective clinical cohort, the Sahlgrenska CardioMyoPathy Centre (SCMPC) study, and compare patients with cardiomyopathies in terms of phenotype, symptoms, and survival.MethodsThe SCMPC study was founded in 2018 by including patients with all types of suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…According to symptoms distribution, the present study showed that there were 7 patients who had acute chest pain (14%), 13 patients (26%) had dyspnea, and 13 patients (26%) had lower limb edema. According to a recent study by Ljungman et al (14) , the kind of cardiomyopathy had some influence on the first symptoms. The cohort's most prevalent symptom at beginning was dyspnea (63.3%), which was followed by exhaustion (51.9%) and chest discomfort (30.5%).…”
Section: ------------------------------------------------------------...mentioning
confidence: 98%
“…According to symptoms distribution, the present study showed that there were 7 patients who had acute chest pain (14%), 13 patients (26%) had dyspnea, and 13 patients (26%) had lower limb edema. According to a recent study by Ljungman et al (14) , the kind of cardiomyopathy had some influence on the first symptoms. The cohort's most prevalent symptom at beginning was dyspnea (63.3%), which was followed by exhaustion (51.9%) and chest discomfort (30.5%).…”
Section: ------------------------------------------------------------...mentioning
confidence: 98%